Separable states and positive maps II - Størmer, Erling (Mathematica Scandinavica, 2009)
Using the natural duality between linear functionals on tensor products of C^*-algebras with the trace class operators on a Hilbert space H and linear maps of the C^*-algebra into B(H), we give two characterizations of separability, one relating it to abelianness of the definite set of the map, and one on tensor products of nuclear and UHF C^*-algebras.